Gram-Scale Synthesis of 3,5-Methanonipecotic Acid, a Nonchiral Bicyclic β-Amino Acid - Tymtsunik, Andriy V.; Bilenko, Vitaliy A.; Grygorenko, Oleksandr O.; Komarov, Igor V. (Synlett, 2014)
A scalable synthesis was developed of 3,5-methanonipecotic acid (3-azabicyclo[3.1.1]heptane-1-carboxylic acid), a rare example of a conformationally constrained nonchiral β-amino acid, potentially useful in peptide engineering and peptidomimetic drug design. A retrosynthetic strategy based on disconnections exclusively within the symmetry planes of the target and the intermediate molecules was found to be useful and might deliver expedite syntheses in other similar cases.
Keywords: amino acids; bicyclic compounds; heterocycles; conformation